Hydrolysate as an alternative feedstock for furfural production - Utami, Syelvia Putri; Rezki, Yoanni Marsha; Ermalinda, Vina; Komalasari; Aziz, Yelmida (BRIN Publishing (Penerbit BRIN), 2024)
Furfural has emerged as a value-added chemical product which generated from hemicellulose-base biomass, in the context of hardwood it called as biorefining. Several methods have been developed to produce furfural using both hydrothermal and catalytic processes. In this study, hydrolysate is used as feedstock for generating furfural by using diluted sulfuric acid and aluminium chloride. Temperature and reaction time has been considered as the valuable variable. Hydrolysate was charged with the acid-catalyst for around 90 min at certain temperature. The product analyzed by using fourier transform index refractory and excess bromine method. At this time, the highest yield of furfural for non-catalyst process was achieved at 120 oC for 90 min. Diluted acid solution by hydrochloric acid and AlCl3 1% managed to increase furfural production from hydrolysate in the mild temperature.